2003
DOI: 10.2320/matertrans.44.53
|View full text |Cite
|
Sign up to set email alerts
|

Anelasticity Study on Motions of Atoms in the Grain Boundary Regions in Nanocrystalline Gold

Abstract: High-density nanocrystalline (n-) Au was prepared by the gas deposition method. Various anelastic and plastic creep processes associated with the grain boundary (GB) regions were observed. The vibrating reed measurements at 10 2 Hz with strain amplitude of 10 À6 show a very broad internal friction peak near 95 K, Q À1 p,95 K , and a steep increase in the anelastic strain above 200 K, " a-I,>200 K . The tensile tests show a steep increase in the anelastic strain above 200 K, " a-II,>200 K , for the stress beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Therefore we suggest that the contrast changes could be due to grain rotation or sliding due to dislocation activities at the grain boundaries. For grain sizes smaller than that reported in this study, the inverse dependence of this ratio with grain size predicts pronounced effects of the grain boundary diffusion that can possibly introduce anelasticity at the room temperature, as observed in other studies [17,22].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore we suggest that the contrast changes could be due to grain rotation or sliding due to dislocation activities at the grain boundaries. For grain sizes smaller than that reported in this study, the inverse dependence of this ratio with grain size predicts pronounced effects of the grain boundary diffusion that can possibly introduce anelasticity at the room temperature, as observed in other studies [17,22].…”
Section: Resultsmentioning
confidence: 64%
“…However, the number of thermomechanical studies involving freestanding thin films is rather limited [14,15], which provides the motivation for studying mechanical properties of freestanding thin films at elevated temperatures. It is important to note that similar studies on bulk nano-crystalline materials have provided significant insight on the length-scale and temperature dependence of the mechanical properties at the nano-scale [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Further, " an,>200 K -II is also associated with a certain anelastic process in the GB regions because it can be observed in n-Au specimens but not in poly-Au specimens. A certain characteristic process associated with several atoms in the GB of the n-metals appears to be responsible for " an,>200 K -I and " an,>200 K -II, 6,33) however, the detailed mechanisms are not known at the present.…”
Section: Nmmentioning
confidence: 94%
“…In the gas deposition method, ultrafine metallic particles formed by the inert-gas condensation process were directly deposited on a glass substrate by using a He gas jet-flow 5 . The purity of He used for the gas condensation and jet-flow was kept better than 99.9999% by a purification system.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The internal friction measurement is a powerful and sensitive tool to study behavior of the grain boundaries. For the elasticity measurement, we reported that the internal friction of n-Au showed a rapid increase linearly with temperature above 200 K accompanied with a decrease in dynamic Young's modulus 5,6 . Since the amount became small with a progress of the grain growth by annealing, the rapid increase of internal friction above 200 K was attributed to a certain anelastic relaxation process in the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%